2014
DOI: 10.1007/s00484-014-0924-3
|View full text |Cite
|
Sign up to set email alerts
|

The association of extreme temperatures and the incidence of tuberculosis in Japan

Abstract: Seasonal variation in the incidence of tuberculosis (TB) has been widely assumed. However, few studies have investigated the association between extreme temperatures and the incidence of TB. We collected data on cases of TB and mean temperature in Fukuoka, Japan for 2008-2012 and used time-series analyses to assess the possible relationship of extreme temperatures with TB incident cases, adjusting for seasonal and interannual variation. Our analysis revealed that the occurrence of extreme heat temperature even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
28
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 31 publications
7
28
1
Order By: Relevance
“…Hospital admissions in colder months are significantly higher than in warmer months [17,18], however the occurrence of extremely high temperatures during the summer has resulted in a significant increase in the number of tuberculosis cases [19]. Moreover, air pollution is a substantial cause of morbidity and mortality worldwide [20].…”
Section: Introductionmentioning
confidence: 99%
“…Hospital admissions in colder months are significantly higher than in warmer months [17,18], however the occurrence of extremely high temperatures during the summer has resulted in a significant increase in the number of tuberculosis cases [19]. Moreover, air pollution is a substantial cause of morbidity and mortality worldwide [20].…”
Section: Introductionmentioning
confidence: 99%
“…Referring to the previous study (Onozuka andHagihara, 2015, Xiao et al, 2018) and GACV values, we set a maximum lag structure as 70 days (10 weeks) as it also is longer than the incubation period (4-8weeks). We used mean value of T mean (15.0℃) as the reference to calculate the relative risks (RRs), and used the minimum, the 5 th and 25 th of percentiles temperature as the cold temperature effect and the maximum, the 95 th and 75 th of percentiles as the hot effect.…”
Section: Discussionmentioning
confidence: 99%
“…Further, it has been shown that the risk of TB has a correlation with climate and extreme heat or cold temperatures. [14,15] Due to the diversity of temperature ranges and fluctuations, climate types, and economic environments in different regions, the relationships between temperature and TB in different regions should be studied and will provide important evidence also for other countries.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a lot of studies in different regions put forward that other environmental factors can also exert an effect on TB incidence. For example, the areas with extra dry climate are high-risk regions of TB [14]; the decrease of SD lead to an increased risk of TB [16]; the TB incidence are positively associated with the WS [17,18]. The meteorological and environmental factors are some of the central variables affecting the airborne transmission of pathogens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation